Concepts and Implementation in Multiple Business Systems: Study in Village Unit Cooperatives, Pangkalan Tiga, Central Kalimantan - Akbar, Wahyu; Frasetia, Anggi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The study’s goal is to map out the complex commercial infrastructure of KUD Tani Subur, as well as to learn how the multi-business system in KUD Tani Fertile has affected the well-being of its members and the Pangkalan Tiga village community. This research uses a qualitative, descriptive methodology in the field. Cooperative leaders, cooperative members, and the residents of Pangkalan Tiga served as participants in this study. Selective sampling strategies for identifying study subjects. Sources of information for this study were interviews, observations, and written records. The data were examined descriptively, taking into account system theory and welfare in the framework of Sharia economics. This research leads us to the conclusion that KUD Tani Subur operates on an Islamic economic profit-sharing paradigm, in which 30% of business profits are used to fund the growth of KUD Tani Subur, and 70% are distributed among members, social funds, and other charitable organizations. Members and the surrounding community of Pangkalan Tiga village welfare monetarily and spiritually from the all-business structure.